Kesiapan Bank Syariah dalam Menghadapi Resesi 2023 - Bahtiar Effendi Effendi (ITB AAS INDONESIA Surakarta, 2023)
The global recession of 2023 is predicted to occur in plain sight. If it really happens, the impact will be widespread on various sectors of life, one of which is the financial sector which is the heart of the economy. This research was conducted with the aim of seeing the readiness of Islamic banks in facing the 2023 recession. The methods used in this research are descriptive qualitative methods and library research. This method is used to explain and analyze the object of research to match the reality that occurs so that the author can explore more deeply and can review in detail how the experience of Islamic banks in responding to the previous recession that has occurred in Indonesia. The data used in this research are secondary data such as journal articles, books, websites, and news that have relevance in this study. The results of the study explained that based on experience and statistical data, the Islamic banking sector is predicted to be resistant to the shock of the 2023 recession. One of the things that can hinder banking growth is NPF, but judging from the existing data, the NPF of Islamic banks tends to be low, so it can be said that the financial condition of Islamic banks is still healthy even though last year was affected by the pandemic. In facing the 2023 recession, the government has an important role in its policies to anticipate the impact of the recession, although the Indonesian economy is still growing above 5% but must be vigilant, especially against the storm of layoffs that has recently hit a number of companies. The public is also urged to anticipate the impact of the recession, starting from preparing an emergency fund, not making waste, and making investments.